Enhancing children’s literacy learning: from invented spelling to effective reading and writing - Albuquerque, Ana (2019)
This longitudinal study aimed at testing the long-term impact of invented spelling activities conducted in kindergarten on children’s literacy skills throughout primary school until the end of Grade 3. The participants were 100 Portuguese 5-year-olds that were randomly assigned into two equivalent groups and took part in 10 training sessions: invented spelling (experimental condition) or storybook reading (control condition). Writing and reading skills were tested in kindergarten, Grade 1 and Grade 3. The results showed that the experimental group outperformed the control group in kindergarten and benefited more from formal school teaching instruction. Lasting effects were found as the invented spelling condition presented statistically significant higher scores in reading and writing in primary education. These findings support empirical evidence for enhancing young children’s learning in favour of their later literacy performance.